Biochemical evaluation of glycemic levels of long-term tacrolimus therapy in rats Avaliação bioquímica dos níves glicêmicos da terapia com tacrolimo por longo período em ratos - Carlos Augusto Nassar; Patricia Oehlmeyer Nassar; Denise Carleto Andia; Morgana Rodrigues Guimarães; Maria Teresa Pepato; Luis Carlos Spolidorio (Sociedade Brasileira de Pesquisa Odontológica, 2007)
One of the more serious complications following transplantation is the development of post-transplantation diabetes mellitus (PTDM), which has a major impact on the quality of life, with effects ranging from the control of glycemia times to increased susceptibility to infections and cardiovascular complications. It has been suggested that immunosuppressive therapy, mainly tacrolimus therapy, may be an important factor in the development of PTDM. There is a lack of studies that explore the effects of long-term tacrolimus on PTDM in animal protocols. The objective of this study was therefore to evaluate the effects of long-term therapy with tacrolimus in rats. One group was treated with tacrolimus, injected subcutaneously, in a daily dose of 1 mg/kg of body weight. The chosen dose was sufficient to achieve therapeutic tacrolimus serum levels. The experimental periods were 60, 120, 180 and 240 days. One group was used as control and received daily subcutaneous injections of saline solution during all periods. A tendency towards increased glycemia levels during the initial periods (60 and 120 days) was observed. However, at 180 and 240 days, the glycemia levels were not statistically different from that of the control group of the same period. It may thus be concluded that the deleterious effects of tacrolimus therapy on glycemia may be a time-related side effect. Uma das mais sérias complicações pós-transplante é o desenvolvimento de Diabetes Mellitus Pós-Transplante (DMPT), que irá produzir um grande impacto na qualidade de vida, com variações do controle glicêmico, aumentando a susceptibilidade a infecções e complicações cardiovasculares. Tem sido sugerido que a terapia imunossupressora, principalmente com tacrolimo, pode ser um importante fator no desenvolvimento de DMPT. Existem atualmente poucos estudos explorando os efeitos de um longo período de terapia com tacrolimo sobre DMPT em protocolos animais. Portanto, o objetivo deste estudo foi avaliar o efeito glicêmico de uma terapia por longo período com tacrolimo em ratos. Um grupo foi tratado com tacrolimo com doses diárias subcutâneas de 1 mg/kg de peso corporal. A escolha dessa dose foi suficiente para a obtenção dos níveis séricos terapêuticos desejados com tacrolimo. Os períodos experimentais foram 60, 120, 180 e 240 dias. Outro grupo foi usado como controle e recebeu injeções salinas subcutâneas diariamente durante todos os períodos. Houve uma tendência ao aumento do nível glicêmico nos períodos iniciais (60 e 120 dias). Entretanto, após 180 e 240 dias, os níveis de glicemia não foram estatisticamente diferentes dos obtidos nos grupos controles de mesmo período. Assim, pode-se concluir que os efeitos glicêmicos adversos provocados pela terapia com tacrolimo podem ser relacionados ao tempo.